A Holistic Approach to the Efficient Estimation of Operational Flexibility From Distributed Resources - Nikolaos Savvopoulos; Nikos Hatziargyriou; Hannu Laaksonen (IEEE Open Access Journal of Power and Energy)
The integration of Distributed Energy Resources (DER) like renewable generation into the power system has increased the need to develop effective strategies for procurement of flexibility services from these distribution network connected resources. In order to realize the flexibility potential of DERs to support flexibility needs of the system operators, the aggregated available flexibility at the interconnection point between transmission and distribution system needs to be estimated. This paper presents a novel optimization-based method to estimate the time-dependent flexibility at a primary distribution substation while accounting for the uncertainty of renewable generation. The proposed approach integrates the stochasticity of the flexibility resources using a scenario-based robust optimization and incorporates the intertemporal constraints of DER into the estimation process, ensuring a realistic representation of the flexibility capability over time. The scenarios are derived through sampling from a probability distribution of the renewable energy forecasts. This process utilizes a joint probability distribution and copulas to account for the temporal and spatial correlation among the renewable energy sources of the same region. Based on the joint hourly probability of the different scenarios a robust solution is finally obtained according to the assumed confidence level.